2011
DOI: 10.1007/s10439-011-0337-y
|View full text |Cite
|
Sign up to set email alerts
|

Combined Experimental and Mathematical Approach for Development of Microfabrication-Based Cancer Migration Assay

Abstract: Migration of cancer cells is a key determinant of metastasis, which is correlated with poor prognosis in patients. Evidence shows that cancer cell motility is regulated by stromal cell interactions. To quantify the role of homotypic and heterotypic cell-cell interaction on migration, a two-dimensional migration assay has been developed by microfabrication techniques. Two breast cancer cell lines, MDA-MB-231 and MDA-MB-453, were used to develop micropatterns of cancer cells (cell islands) that revealed distinct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…Many cell isolation and migration microfluidic chips and other devices have been reported in recent years 6 – 11 , 22 31 . Many microfluidic chip structures have been designed and fabricated to display the advantage of microfluidics no regardless of whether they include large numbers of cells or a single cell.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many cell isolation and migration microfluidic chips and other devices have been reported in recent years 6 – 11 , 22 31 . Many microfluidic chip structures have been designed and fabricated to display the advantage of microfluidics no regardless of whether they include large numbers of cells or a single cell.…”
Section: Discussionmentioning
confidence: 99%
“…To date, with the development of microfabrication technology, microfluidic chips have emerged as a revolutionary, novel platform for many applications in cell biology, bionic organs, cell and particle sorting and disease detection 15 21 . Microfluidics-based wound-healing assays have been proposed as effective tools for studying cell migration, which can mimic in vivo microenvironments more closely than conventional wound-healing assays 22 25 . Advances in microfluidics techniques have allowed for cell migration assays on a simple microfluidic chip by replicating the traditional biological laboratory 26 – 30 .…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, the predictive capabilities of these models would prove to be extremely useful for understanding the patho-physiological mechanisms of diseases too. A few studies have reported miniaturized in vitro models for studying the diseased state, such 70 as lung injury [78], endothelial cells-circulating tumor cell interaction [79], as well as tumors [80][81][82][83][84]. Huh et al, 2007 [79]described an in vitro model of the human small airway to reproduce under flow conditions cellular level lung injury, which causes symptoms that are characteristic of 75 some pulmonary diseases [ Fig.…”
Section: Disease Modelsmentioning
confidence: 99%
“…The possibility to mimic complex in vivo environments makes microfabrication ideally suited to study essential stages of cancer progression that rely on a complex communication with other cells, such as capillary morphogenesis and cancer cell metastasis [212]. For example, Sarkar, et al developed a simple breast cancer system with cells present as single cells and colonies in an array surrounded by fibroblasts to study the role of homo- and heterotypic cell-adhesion in cell migration [213]. Chung, et al used a system in which cells can migrate within a collagen I scaffold to investigate in detail the effect of cancer cells on the migration of endothelial cells, the first stage of capillary morphogenesis [214].…”
Section: The Application Of Microfabricated Model Systems For Cellmentioning
confidence: 99%